Redefining Khabar Al-Ahad Based on Rashid Rida’s Rational Approach in Al-Manar - Bin Salman, Abdul Matin; Baihaqi, Yusuf; Kusnadi (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2022)
This paper discusses the Rida controversy with hadith scholars. The controversy stems from Rida’s a priori to the traditions that are popular and well-known among hadith scholars, especially the category of khabar al-ahad hadith. The root of their problem lies in Rida’s rational critique of the categories and implications of khabar al-ahad. He considers dilalah (connotation) of khabar al-ahad to be nothing more than just zanni al-dilalah (presumption and uncertainty). The implication is that hadith in this category cannot be used as a basis for belief because belief is based on qat’i al-dilalah (certainty of proposition). The research method used was descriptive-analytic method. This method was combined with a historical-philosophical approach. Therefore, analyzing and describing Rida’s thoughts as a whole is the main work in this article. The next step was to combine the analytical-philosophical approach to the roadmap from the genuine part of Rida’s line of thought. This activity is expected to help the author in finding answers on how Rida rationalizes khabar al-ahad and its implications. Finally, this article finds the conclusions, including: a) Rida’s efforts in rationalizing khabar al-ahad are based on the views of the mutakallimūn (theologians), manat}iqah (logic experts) and falasifah (philosophers), b) Rida has been trapped in his own over a priori thinking on khabar al-ahad, c) Rashid Rida’s rationalization of khabar al-ahad actually leads to ambiguity and uncertainty.